Monitoring intracellular, interstitial, and intravascular volume changes during fluid management procedures - Montgomery, Leslie D.; Gerth, Wayne A.; Montgomery, Richard W.; Lew, Susie Q.; Klein, Michael M.; Stewart, Julian M.; Velasquez, Manuel T. (Medical & biological engineering & computing, 2013)
The bioimpedance spectroscopic (BIS) analytical algorithm described in this report allows for the non-invasive measurement of intravascular, interstitial, and intracellular volume changes during various fluid management procedures. The purpose of this study was to test clinical use feasibility and to demonstrate the validity of the BIS algorithm in computing compartmental volume shifts in human subjects undergoing fluid management treatment. Validation was performed using volume changes recorded from 20 end stage renal disease patients. The validation procedure involved mathematically deriving post hoc hematocrit profiles from the BIS data-generated fluid redistribution time profiles. These derived hematocrit profiles were then compared to serial hematocrit values measured simultaneously by a CritLine ® monitor during 60 routine hemodialysis sessions. Regression and Bland–Altman analyses confirm that the BIS algorithm can be used to reliably derive the continuous and real-time rates of change of the compartmental fluid volumes. Regression results yielded a R 2 > 0.99 between the two measures of hematocrit at different times during dialysis. The slopes of the regression equations at the different times were nearly identical, demonstrating an almost one-to-one correspondence between the BIS and CritLine ® hematocrits. Bland–Altman analysis show that the BIS algorithm can be used interchangeably with the CritLine ® monitor for the measurement of hematocrit. The present study demonstrates for the first time that BIS can provide real-time continuous measurements of compartmental intravascular, interstitial and intracellular fluid volume changes during fluid management procedures when used in conjunction with this new algorithm.